PERBEDAAN KADAR HEMOGLOBIN SEBELUM DAN SESUDAH AKTIVITAS FISIK BERAT - indah sari (IKesT Muhammadiyah Palembang, 2023)
Introduction: Hemoglobin is an erythrocyte tetrameric protein that binds to a non-protein molecule, the Iron porphyrin compound called heme. The most important function of hemoglobin is transporting oxygen (O2) from the lungs to the peripheral tissues and transporting carbon dioxide (CO2) from the tissues to the lungs for exhalation to the outside. Factors that affect hemoglobin levels one of physical activity. Strenuous physical activity that releases a lot of sweat such as aerobics, cycling (19 – 22 km/h), swimming, tennis and running. The study aimed to determine the difference in hemoglobin levels before and after heavy physical activity in the form of running for 5 minutes with a heart rate frequency > 145 times/minute. Method: data analysis using Paired Sample T-Test SPSS. This research was conducted at the Muhammadiyah Institute of Health Sciences and Technology Palembang in March 2021 with a total of 32 respondent. Results: the average hemoglobin levels before physical activity is 15,1 g/dL while hemoglobin levels after heavy physical activity is 15,3 g/dL, based on the Test Paired Sample t-Test get p > 0.05 that is no difference between the two. Discussion: there was no difference between hemoglobin levels before and after heavy physical activity.